Interspecies Sex and Taste - Koh, Tong-Wey (2013)
Different species of fruit flies share habitats but are believed to mate with each other only rarely. In this issue, Fan et al. show that interspecies mating is inhibited by the taste receptor Gr32a (Gustatory receptor 32a) and a neural circuit in which it functions.